Education policy as a roadmap for achieving the sustainable development goals : effecting a paradigm shift for peace and prosperity through new partnerships - Taysum, Alison (Emerald Publishing Limited, 2019)
The 17 Sustainable Development Goals (SDGs) have been agreed globally as an unprecedented, ambitious and innovative agenda for prosperity and peace for people and the planet. Currently researchers, policymakers and nations are trying to identify clear routes for achieving these ambitious goals by 2030. This timely text examines how education policy provides a roadmap to achieving Sustainable Development Goal 4, achieving inclusive and equitable quality education and promoting lifelong learning opportunities for all. Taysum situates the SDGs, and the roadmap to achieving them, within a historical framework of established philosophy by drawing upon the ideas of the social contract, moral values and universal principles. As well as offering a theoretical understanding of these concepts, this research also offers practical solutions by demonstrating how university Vice Chancellors, Deans of Faculties and Schools of Education can work in partnership with the wider community in order to achieve the SDGs. Supported by a website and rich bank of practical resources, this book will prove invaluable for education leaders and those in the fields of higher education and moral philosophy.